Chemical Nature and Water Quality of Jakekur Reservoir (Project) in Context with Drinking Water Standards - Ugale, B. J. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
The Jakekur Reservoir is one of the most important aquatic water bodies in Ta. Omerga Dist. Osmanabad (M.S). The reservoir is used for irrigation, Drinking purpose, as well as pisciculture by the local communities. Limnological investigations of man-made lakes (reservoirs) are necessary to evaluate water quality is related to the health of people, ecosystem, societies, and potential fish production. It provides information that could be useful in fisheries developmental planning and it is supply for Domestic, Industrial, Agriculture & aquaculture practices. Reservoir has large and varied chemical contents. Innumerable materials enter the system from the atmosphere, catchments area and its own basin. The chemical properties of reservoir not only alter but also have significant bearing on the distribution and metabolic activities of the existing life. During the study period samples were collected from the reservoir for a period of one year. From result it is concluded that sample result was within permissible limits in context with drinking water standards as described by Bureau of Indian Standard for Drinking Water for Water Quality Standards.